Kepemimpinan Pendidikan - Bahrul Amin (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2014)
Globalization is the occurrence change in various aspects of human life. Globalization is characterized by advances in information technology and all of the information can be accessed easily and quickly. During the development, globalization causes many problems in the field of culture. Such as the loss of the original culture of a country, the decline in the sense of nationalism and patriotism, lifestyle changes, and so on. To anticipate these conditions, in a public organization such as a state need a leader who understands the running cross-cultural leadership. The researches team from GLOBE has done several researches about the relationship between culture and leadership. The main objective of this research is to improve our understanding of cross-cultural interaction and cultural impact on leadership effectiveness. As part of their study of culture and leadership, GLOBE researchers develop their own classification of cultural dimensions. Transformational leadership is a leadership approach to doing business to increase awareness, excite and inspire subordinates or members of the organization to expend extra effort in achieving organizational goals. A leader is known as a transformational leader if he can change he situation, has a lofty goals, and has a reference value of freedom, justice and equality. Transformational leadership is the kind of leadership needed in globalization era.